A 6-month, prospective randomized controlled trial of the TargetEd MAnageMent (TEAM) intervention vs. enhanced treatment as usual among Ugandans at risk for stroke - Mark Kaddumukasa; Martin Kaddumukasa; Scovia Nalugo Mbalinda; Josephine Najjuma; Jane Nakibuuka; Doreen Birungi; Carla Conroy; Joy Yala; Levicatus Mugenyi; Christopher J. Burant; Shirley Moore; Elly T. Katabira; et al. (PLoS ONE, 2025)
Background Among low and middle-income countries, especially in Sub-Saharan Africa, the stroke burden is severe, with increasing trends in stroke incidence, prevalence, and mortality. Aims This 6-month, prospective randomized controlled trial (RCT) compared a novel stroke risk reduction approach (TargetEd manAgeMent Intervention (TEAM)) vs. Enhanced Treatment as Usual (ETAU) in 247 Ugandans at risk for stroke. Methods Participants, enrolled across 3 Ugandan sites, were adults with high stroke risk. The primary outcome was a change in systolic blood pressure (SBP) from baseline to 6-month follow-up. Secondary outcomes included changes from baseline to 6 months on diastolic BP (DBP), serum lipids, glycosylated hemoglobin (HbA1c), self-efficacy and stress. Results The mean sample age was 55.4 (±SD = 12.0) with majority being women (n = 168, 68%). In addition to hypertension, the most common risk factors were hyperlipidemia (n = 199, 80.6%) and obesity (n = 98, 39.7%). Overall mean SBP and DBP at baseline were 143.0 (SD = 19.8, range 94.5–206) and 89.3 (SD = 14.0, range 61–136) respectively. In TEAM, SBP significantly improved from 145.7 (±21.5) at baseline to137.4 (±18.1) at 6-months vs. change from 141.9 (±18.4) to 141.1 (±21.9) for ETAU (p = 0.031). There were similar reductions in DBP favoring TEAM (p = .012). Compared to ETAU, TEAM showed improved physical activity (p = .017), self-efficacy (p < .001) and stress (p = .014). Conclusions There is a need for effective and practical approaches to reduce stroke burden in Sub-Saharan Africa. Inclusion of the TEAM approach in primary care seems to be a pragmatic and effective way to potentially reduce stroke burden in Uganda. Trial registration ClinicalTrials.gov identifier: NCT04685408, registered on 28 December 2020.